DOES TRUST AND HEDONIC OTIVATION ENHANCE PURCHASE INTENTION? DOES TRUST AND HEDONIC OTIVATION ENHANCE PURCHASE INTENTION? - Benedict Valentine Arulanandam; Helma Malini; Fiola Oktaningtias (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
Abstract: The purpose of this study is to define the influence of Hedonic Motivation, Instagram Stories Features and Trust to Consumer Purchase Intention. This work uses a quantitative approach to the study of data using multiple linear regression approaches. The participants in this analysis are women aged 20 to >25 years of age. The findings of this study are that Hedonic Motivation, Instagram Stories Features and Trust have a significant positive effect on Purchase Intention. The findings of the analysis showed that the three independent variables had a major positive effect. Hedonic Motivation, Instagram Stories Features and Trust have a major positive impact on Purchase Intention at a 5% point of significance. Keywords: Hedonic Motivation, Instagram Stories Features, Trust, Consumer Purchase Intention.